Analisis Kelayakan Bisnis dan Perancangan Produk Pada Lemari Plastik Multifungsi - Geraldo Cikal Sunakalis; Wahyudin Wahyudin; Lugina Lestari (Peneliti.net, 2022)
This study discusses the design of multifunctional plastik wardrobe products based on consumer demand and a business feasibility study for multifunctional plastik wardrobe products to be run in Cikarang. The method used is quantitative by using the Quality Function Deployment (QFD) as well as business feasibility aspects. The data required includes product dimensions, while a business feasibility study requires data on the cost of capital, demand and supply for the years 2021-2023. The results of QFD processing show that there are 3 factors and 2 dimensions of the product whose importance is owned by high quality attributes, while the results of the calculation of the business feasibility study show that this business is feasible / feasible to run on this basis based on the feasibility aspect of the business.